Design and Performance Analysis of a Compact Series Elastic Actuator for Exoskeletons - de Gaitani, F. H.M. [UNESP]; dos Santos, W. M. [UNESP]; Siqueira, A. A.G. (Springer Nature, 2022)
In this paper, a compact Series Elastic Actuator is designed and evaluated. The proposed actuator will be used to drive the joints of the modular exoskeleton for lower limbs ExoTAO (Transparent Active Orthosis), available at the Robotic Rehabilitation Laboratory of EESC/USP. This equipment is being developed to assist in the rehabilitation of people with motor disabilities resulting from injuries to the central nervous system or to the spinal cord. The differential of the proposed actuator is the use of a customized and compact torsion spring, providing the necessary levels of torque and velocity to drive the exoskeleton. Such performance levels were evaluated considering the characteristics of the selected components and the gait patterns available in the literature. In addition to the theoretical analysis, experimental tests were also conducted with the actuator in order to evaluate its performance in achieving a satisfactory torque control. Time and frequency responses show the proposed actuator is able to reproduce the necessary torque to drive the exoskeleton ExoTAO, achieving high bandwidth values.
Keywords: Exoskeleton; Orthosis; Rehabilitation; Robotic; Series elastic actuator